MAHARAH QIRĀ'AH EXERCISES IN THE INDONESIAN MINISTRY OF RELIGIOUS AFFAIRS ARABIC TEXTBOOK FOR MTs: AN ANALYSIS BASED ON H. DOUGLAS BROWN'S READING SKILLS FRAMEWORK: "Latihan Maharah Qira'ah dalam Buku Ajar Bahasa Arab MTs Kementerian Agama Republik Indonesia: Analisis Berdasarkan Kerangka Keterampilan Membaca H. Douglas Brown - hamzah, muhammad abi; Rosyidi, Abdul Wahab; Mufidah, Nuril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading skill (maharah qirā'ah) plays an important role in Arabic language learning, particularly in helping students understand written texts effectively. Therefore, reading exercises in Arabic textbooks should reflect appropriate reading skill frameworks. This study aims to analyze the maharah qirā'ah exercises in the Grade VIII Arabic textbook published by the Indonesian Ministry of Religious Affairs based on H. Douglas Brown's reading skills framework. This study employed a qualitative approach using content analysis. The data were collected from reading materials, vocabulary lists, and exercises contained in the textbook and analyzed using Krippendorff's six-stage content analysis procedure. The findings reveal that the textbook contains fourteen qirā'ah exercises distributed into two reading skill types: selective reading and interactive reading, each accounting for seven exercises (50%). Meanwhile, perceptive reading and extensive reading were not identified in the textbook. The absence of perceptive reading tasks is considered appropriate for students' level, while the absence of extensive reading indicates limited opportunities for students to develop higher-level reading skills. This study concludes that the qirā'ah exercises in the Grade VIII Arabic textbook partially reflect Brown's reading skills framework but lack comprehensive coverage of all reading skill types. Therefore, teachers are encouraged to supplement the textbook with extensive reading activities to support balanced development of students' Arabic reading skills.